The use of topical zinc in tuberculin test - Anisa Rahmadhany; Darmawan Budi Setyanto; Partini Pudjiastuti Trihono (Paediatrica Indonesiana, 2013)
with under-diagnosis or over-diagnosis commonly occurring. The tuberculin test as a supporting examination for tuberculosis infection has a false negative value rate of 10-25%. Also, a majority of children with tuberculosis have lower plasma zinc levels than healthy children. Zinc deficiency may impair the immune response, leading to more false negative skin-test results.Objective To evaluate the effectiveness of topical zinc for augmenting the diameter of tuberculin induration in children with tuberculosis.Methods This unblinded, clinical trial was performed from October to December 2012 in subjects matched with themselves. Subjects were children with tuberculosis aged 2-18 years at the Department of Child Health at Cipto Mangunkusumo Hospital and Persahabatan Hospital. Every subject was injected tuberculin in volar region of left and right arm. Test sites then were covered with topical zinc cream on the right arm and placebo cream on the left arm. Indurations were measured after 72 hours. The difference of tuberculin diameter of 3 mm was considered as clinically significant. Data analysis was performed with Wilcoxon signed rank test.Results There were 47 subjects in this study. The majority of subjects were well-nourished (53%). Subjects’ median treatment duration was < 6 months, median age was 72 months and 47% of subjects were under the age of five years. Sixteen subjects had a median 1 mm difference in tuberculin induration diameter between the zinc arm and placebo arm (P<0.001), but this was clinically insignificant. Twenty-two subjects (43%) had Koch reaction after zinc cream application, but the placebo cream did not cause Koch reaction.Conclusion Application of topical zinc does not increase tuberculin induration compared to placebo.